Drugs, society, and human behavior - Hart, Carl L.
Drugs, Society and Human Behavior provides the latest information on drug use and its effects on society as well as on the individual. Trusted for more than 30 years by both instructors and students, this authoritative resource examines drugs and drug use from a variety of perspectivesbehavioral, pharmacological, historical, social, legal, and clinical. The text not only gives students the tools and information to make better personal decisions about psychoactive substances but also promotes a deeper understanding of the individual problems and social conflicts that arise when others misuse and abuse these substances. Accompanying the text are instructor and student resources on the Online Learning Center